2015
DOI: 10.3389/fmars.2015.00029
|View full text |Cite
|
Sign up to set email alerts
|

Modeling species invasions using thermal and trophic niche dynamics under climate change

Abstract: Changing marine temperatures modify the distributional ranges of natural populations, but the success of invasion of new areas depends on local physical and ecological conditions. We explore the invasion by thermophilic species and their ecosystem effects by simulating a sea surface temperature (SST) increase using a trophodynamic model for the northern Adriatic Sea (NAS), in which thermal and trophic niches are explicitly represented for each thermophilic non-indigenous species (NIS) and native species. The N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 54 publications
1
48
1
1
Order By: Relevance
“…but also due to indirect interactions of mixed fisheries (Walters et al, 2005;Mackinson et al, 2009), especially in a fast changing ecosystem such as the Mediterranean. The rapid warming, combined with the expansion of non-indigenous species is definitely changing the suitability of the habitats for traditional commercial species with effects on their resilience to fishing (Libralato et al, 2015). The recent collapse of small pelagic fishery in the Gulf of Lions is a clear example where poor fish growth, size and body condition and ultimately biomass seem to be due to bottom-up control characterized by changes in food availability and increasing potential trophic competition (Brosset et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…but also due to indirect interactions of mixed fisheries (Walters et al, 2005;Mackinson et al, 2009), especially in a fast changing ecosystem such as the Mediterranean. The rapid warming, combined with the expansion of non-indigenous species is definitely changing the suitability of the habitats for traditional commercial species with effects on their resilience to fishing (Libralato et al, 2015). The recent collapse of small pelagic fishery in the Gulf of Lions is a clear example where poor fish growth, size and body condition and ultimately biomass seem to be due to bottom-up control characterized by changes in food availability and increasing potential trophic competition (Brosset et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing body of research is showing fast spreading of new invasive species in the Mediterranean (Lejeusne et al, 2009;Galil et al, 2014;Parravicini et al, 2015) that can have indirect effects on resident communities and fisheries difficult to quantify (e.g., Libralato et al, 2015). Pollution and marine litter are having strong attention because of the several indirect and direct impacts on both stocks and fisheries (Galgani, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(e.g., Mutshinda, Finkel, Widdicombe, & Irwin, 2016) and, by describing complex ecological structures, can help disentangle the effects of functional diversity on ecosystem processes (e.g., Holzwarth, Rüger, & Wirth, 2015). Modeling marine food webs has shown great potential for investigating the changes due to environmental variability and climate change (Heymans, Coll, Libralato, Morissette, & Christensen, 2014;Libralato, Caccin, & Pranovi, 2015), exploitation of fishing resources and aquaculture management (Forestal, Coll, Christensen, & Die, 2012;Libralato et al, 2010), as well as pollution, nutrient enrichment and the impact of alien species (Daskalov, 2002;Fulton, 2010;Pranovi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that in some circumstances non‐native species may enrich ecosystems rather than causing harm (Libralato et al, ), and non‐native species can co‐exist with natives in some instances (Gallagher, Culloty, McAllen, & O'Riordan, ). In addition, some of the species considered in this study could represent a hither‐to unexploited commercial opportunity where they have invaded.…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that non‐native species could cost Europe €20 billion per year in damage caused, and in subsequent eradication programmes (Kettunen et al , ). Distributions of non‐native species are often constrained by the available vectors or mechanisms of introduction, and by the environmental conditions of the receiving areas (Libralato, Caccin, & Pranovi, ). The survival and reproduction of marine non‐native species arriving in a new area are constrained by factors such as temperature and salinity, but also depth, substrate type and food availability; and it is thought that climate change may facilitate their persistence or reproduction in locations not previously habitable (Cook et al, ), and that some species may be ‘lying in wait’ until environmental conditions change (Ziska & Dukes, ).…”
Section: Introductionmentioning
confidence: 99%